Richard Pococke's Letters from the East (1737-1740) - Finnegan, Rachel, (The History of Oriental Studies ;, 2021)
In Richard Pococke's Letters from the East (1737-1740) , Rachel Finnegan provides edited transcripts of the full run of correspondence from Richard Pococke's famous eastern voyage from 1737-41. In this new volume, Finnegan combines updated biographical accounts of the traveller and his correspondents (his mother, Elizabeth Pococke and his uncle and patron, Bishop Thomas Milles) from vol. 1 of the original edition of Letters from Abroad (2011) with transcriptions of the letters from vol. 3 of the series (2013), together with new material that has hitherto been unpublished. Thus, in a single volume, she sets the context of the life and times of the traveller and his family against the background of this voluminous corpus of fascinating correspondence, which can be read in conjunction with Pococke's own published account of his travels, A Description of the East and Some Other Countries (1743-45)